Preparation and Thermodynamic Properties of Camphene/Stearic Acid Composites as Phase-Change Materials in Buildings - Canbay, Canan Aksu; Genc, Zuhal Karagoz; Acar, Sureyya Seyma; Sekerci, Memet; Genc, Murat (Springer/Plenum Publishers, 2014)
In this study, a series of shape-stabilized phase-change materials (PCMs) of camphene/stearic acid (CS) were prepared and their thermal properties were measured by differential scanning calorimetry. The results indicated that the mixture consisting of 60 mass% camphene and 40 mass% stearic acid is the most favorable as a PCM, in terms of the phase-change temperature and latent heat. Thereafter, the CS was absorbed in fly ash, pyroclastic, barite, and marble powder, which acts as a supporting material, to prepare four kinds of composite-based PCMs. DSC, FT-IR, and scanning electron microscopy measurements were made to investigate the structures and properties of the PCMs. DSC results showed that the latent heats of melting and freezing of the composite PCMs were sharply decreased. Morphology and structural characterization revealed that, in form-stable PCMs, the dispersion of the supporting materials in the camphene/stearic acid matrix is homogeneous and there is no chemical interaction between the CS and composites. The composite PCMs showed excellent thermal stabilities and reliabilities, when their phase-change temperatures were concerned. These indicate that the prepared composite-based PCMs are suitable for thermal energy storage because of their applicable temperature range, thermal reliability, and chemical stability.
Keywords: Camphene; Form-stable composite PCM; Stearic acid; Thermal energy storage